Tata Laksana Terkini untuk Endometriosis - Binarwan Halim; Timothy Adiwinata (MEDICINUS, 2021)
Endometriosis is a benign gynecological disease that is often found among women in reproductive age with 10% of incidence. There are many theories regarding development of endometriosis, and to date the etiopathogenesis of this disease is still controversial. Understanding the various pathogenesis of endometriosis is important for the management of endometriosis. The current management of endometriosis is still focused on the main symptoms experienced by the patients, such as pain and infertility. A number of therapeutic approaches have been developed based on the pathogenesis of endometriosis, in terms of immunological, angiogenic, hormonal, genetic, local neurogenesis, and central sensitization aspects. However, the ideal and curative treatment for endometriosis has not been found.